Effects of Different Wastewater Irrigation on Soil Properties and Vegetable Productivity in the North China Plain - Zhenjie Du; Shuang Zhao; Yingjun She; Yan Zhang; Jingjing Yuan; Shafeeq Ur Rahman; Xuebin Qi; Yue Xu; Ping Li (Agriculture, 2022)
The interest in reusing wastewater for irrigation is being popularized in most countries. The objective of this study was to evaluate the effects of different wastewater and nitrogen fertilizer on soil fertility and plant quality, as well as to identify the optimal irrigation mode in the North China Plain. A total of nine treatments, including control (groundwater, no fertilizer), piggery wastewater, reclaimed water, and saline water, combined with nitrogen fertilizer (300 kg/ha and 200 kg/ha), were conducted in a greenhouse in 2019 (Xinxiang, Henan Province). Soil pH, electrical conductivity, organic matter, heavy metals contents, and cucumber yield and quality were analyzed. The results showed that: (1) compared with the underground water (control), soil pH value with a decrement of 0.21 units in piggery wastewater (PW), and 0.24 units in saline water treatments (SW). Soil electrical conductivity (EC) value significantly increased by 5.8~20.9% in PW and SW treatments, while there was no significant difference in EC in reclaimed water. The highest EC (770 µS/cm) was recorded in SW treatment. (2) No dramatic difference on the concentrations of soil lead (Pb) and cadmium (Cd) in the PW, RW, and SW treatments, compared with the control, but soil organic matter, copper (Cu), and zinc (Zn) concentrations in wastewater treatments were increased by 2.1~43.4%, 24.4~27.0%, and 14.9~21.9%, respectively. (3) There were no significant differences in cucumber yield and quality in RW treatment, while there was a slight decrease by 1.4% in yield in the SW treatment. The highest cucumber yield was observed in PWH treatment, with an increment of 17.5%. In addition, the contents of Vitamin C, soluble sugar, and protein were also improved by PW treatment. In this study, PW treatment showed the strongest ability to promote cucumber yield and quality, thus indicating that piggery wastewater irrigation with 300 kg/ha nitrogen would be the optimal practice in this region. Long-term study is necessary to monitor potential risk of heavy metals on the quality of soil and plant.